Oxygen-defects modified amorphous Ta2O5 nanoparticles for solar driven hydrogen evolution - Liu, Yong; Zeng, Weixuan; Ma, Yongjin; Dong, Rui; Tan, Pengfei; Pan, Jun (Ceramics international, 2021)
An oxygen-deficient amorphous Ta2O5 nanoparticle photocatalyst was synthesized by a solvothermal method and thermal annealing in Ar atmosphere. The as-prepared Ta2O5 photocatalysts possess improved hydrogen evolution activities compared to pristine Ta2O5 and commercial Ta2O5 under the irradiation of simulated solar light. Therein, Ta2O5 nanoparticles annealing at 400 °C exhibit the most preferable catalytic performance of 10.67 μmol g−1 h−1. The enhanced performance can be attributed to the existence of oxygen defects in the samples, which can facilitate the separation and migration of photogenerated carriers thereby reducing the probability of recombination. [Display omitted]